PEMANFAATAN LAHAN PEKARANGAN OLEH RUMAH TANGGA PETANI DI DESA BULUTELLUE - Herman man man (Jurnal Ilmu Pengetahuan Sosial, 2013)
The issue of food security, including the resilience of rural households more intense lately. This issue started  when governments or communities faced with starvation or disease headquarters with malnourished infants. Seeing this phenomenon, the paper aims to explore and determine the activity and creativity in the face of the village of Bulutellue the issue. The method used is to make observations and interviews with community. The results showed that to overcome the scarcity of basic commodities in the household, the community began to use the land around his home yard to develop plants that are needed for the sake of family consumption. In manage still met the maintenance aspects of the environment to create sustainable rural development